Gut microbiota and relevant metabolites analysis in perianal abscess of infants - Shuai Wang; Jingfeng Zhang; Mingfeng Fan; Zhenmei Dong; Laian Li; Juan Xu; Wanbin Yin; Xiangjun Xu (BMC Microbiology)
Abstract Objectives To explore the characteristics of the gut microbiota and metabolites in infants with perianal abscess compared with healthy infants, thereby providing a reference for treating perianal abscess in infants. Methods The gut microbiota of 19 infants with perianal abscess and 21 healthy infants were compared using 16S rRNA gene sequencing. Metabolite compositions were compared between a subset of 16 infants with perianal abscess and 8 healthy infants. Results Both groups showed significant differences in the abundance of the genera Ruminococcus (P = 0.002) and Parasutterella (P = 0.004). Five metabolic pathways, namely, steroid biosynthesis, one-carbon pool by folate, synthesis, secretion, and action of the parathyroid hormone, cholesterol metabolism, and tuberculosis, were significantly enriched. Three metabolites, namely, calcidiol, dihydrofolic acid, and taurochenodesoxycholic acid, were involved in these enriched pathways. Conclusion The study revealed significant differences in the composition of the gut microbiota and metabolites between healthy infants and those with perianal abscess, suggesting a potential association between the gut microbiota and infantile perianal abscess.